Fenomena Sharing Behavior dalam Media Instagram oleh Remaja Kota Ambon - Sari, Irna Indah; Lestaluhu, Said (Department of Communication Science, University of Pattimura, 2023)
Abstract: Instagram platform is one of the most widely used social media by teenagers today. The number of active Instagram users causes the phenomenon of sharing behavior, this is certainly related to individual motives. This study aims to determine and understand the motivation for sharing behavior on Instagram by teenagers in Ambon City. This research is a qualitative descriptive study. The concept of Oh & Syn (2015) is able to explain ten motivations for sharing behavior including: enjoyment, self-efficacy, learning, personal gain, actruism, empathy, community interest, social attachment, reputation, reciprocity. This research was conducted on students of SMA Negeri 11 Ambon City who were selected purposively and are active users of Instagram. Data collection techniques were carried out through interviews, observations, documentation studies, and literature studies, as well as questionnaires. Data validity is done through triangulation method. The results of the study show that there are several motivations for someone to share on Instagram, namely, because of the need for fun as an effort to seek attention while meeting emotional needs, as an increase in self-confidence by sorting content so that what is displayed is an ideal image, the desire to get new experiences based on content. others, the desire to get a response on the uploaded content. the desire to interact socially with community interest will make a person more sensitive to the surrounding environment and even the emergence of a sense of empathy for oneself to socialize in cyberspace. the desire for recognizing the image of the account owner, and finally the fulfillment of information needs that come from the exchange of information (sharing) between Instagram users. Adolescence is an age that is looking for identity and also needs for self-recognition. It can be concluded that every teenager shares on Instagram the basis of wanting to be famous and look cool and not to be out dated. Keywords: Sharing Behavior, Motivation, Instagram, Recognition